Association between ABCB1 Gene Polymorphisms and Labor Analgesia in Primiparas - Wei Li; Tianke Xiao; Xuehui Wu; Xinyu Wu; Rui Xiang; Haifeng Liu; Jingyi Wang (Clinical and Experimental Obstetrics & Gynecology)
Background: The present study aimed to explore the association of ATP-binding cassette B1 (ABCB1)/multiple drug resistance 1 (MDR1) gene polymorphisms (rs1128503 and rs1045642) with labor analgesia in primiparas. Methods: The cohort comprised 239 primiparas who received epidural analgesia (0.5 μg/L sufentanil + 0.1% ropivacaine). Visual analog scale (VAS) scores were recorded at 0, 1, and 2 h, respectively, after epidural analgesia. The outcomes (VAS score and adverse reactions) of labor analgesia among patients carrying different genotypes of ABCB1 gene polymorphisms were compared using a one-way analysis of variance (ANOVA) or chi-square test. ABCB1 polymorphisms were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The correlation between ABCB1 gene polymorphisms and labor analgesia outcomes (including VAS score and adverse reactions) was evaluated using logistic regression analysis. Results: Genotype distributions of rs1128503 and rs1045642 polymorphisms were detected using Hardy-Weinberg equilibrium (HWE) test. Age, body mass index, and gestational age did not differ significantly between genotypes of rs1128503 and rs1045642 polymorphisms. A higher 2 h-VAS score was observed in the rs1045642 TT genotype than in the rs1045642 CC and CT genotypes, while abnormal fetal heart rate (FHR) monitoring and 1 min Apgar scores were frequently discovered in patients with the rs1128503 TT genotype (p < 0.05). Logistic regression analysis suggested that 2 h-VAS score (p = 0.025, odds ratio (OR) = 0.497, 95% confidence interval (95% CI) = 0.270–0.915), nausea (p = 0.042, OR = 0.188, 95% CI = 0.038–0.940) and Apgar score at 1 min (p = 0.026, OR = 1.774, 95% CI = 1.069–2.942) were distinctly correlated with the rs1128503 TC + CC genotypes. VAS 2 h score (p = 0.000, OR = 3.673, 95% CI = 1.900–7.101) was positively related to the rs1045642 CT + TT genotypes. Conclusions: ABCB1 gene rs1128503 and rs1045642 polymorphisms were significantly correlated with the analgesic effect and adverse reactions of labor analgesia in primiparas.